2015
DOI: 10.3389/fphys.2014.00526
|View full text |Cite
|
Sign up to set email alerts
|

Acute post-exercise change in blood pressure and exercise training response in patients with coronary artery disease

Abstract: We tested the hypothesis that acute post-exercise change in blood pressure (BP) may predict exercise training responses in BP in patients with coronary artery disease (CAD). Patients with CAD (n = 116, age 62 ± 5 years, 85 men) underwent BP assessments at rest and during 10-min recovery following a symptom-limited exercise test before and after the 6-month training intervention (one strength and 3-4 aerobic moderate-intensity exercises weekly). Post-exercise change in systolic BP (SBP) was calculated by subtra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
3
17
0
5
Order By: Relevance
“…Despite these benefits, some subjects present PEH (i. e., "high responders") while others do not (i. e., "low responders"). Interestingly, "high responders" and "low responders" were identified both in non-hypertensive [16,2,31] and hypertensive populations [19,21,24] following different exercise modalities, including aerobic [16,19,21,24] and resistance exercises [21,24,31]. Therefore, it seems that there is a considerable inter-individual BP responsiveness variability following a specific exercise protocol.…”
Section: Introduction ▼mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these benefits, some subjects present PEH (i. e., "high responders") while others do not (i. e., "low responders"). Interestingly, "high responders" and "low responders" were identified both in non-hypertensive [16,2,31] and hypertensive populations [19,21,24] following different exercise modalities, including aerobic [16,19,21,24] and resistance exercises [21,24,31]. Therefore, it seems that there is a considerable inter-individual BP responsiveness variability following a specific exercise protocol.…”
Section: Introduction ▼mentioning
confidence: 99%
“…From a practical perspective, recently PEH has been considered a predictive tool to identify whether or not individuals are responsive to BP reductions with exercise training (i. e., "high" and "low responders") [23]. Previous studies have reported that the magnitude of PEH following a single bout of exercise was correlated with chronic changes in resting BP after a period of exercise training [16,19,22,24,31]. However, it remains unknown whether the same person will have BP responses that are similar when challenged by different exercise protocols.…”
Section: Introduction ▼mentioning
confidence: 99%
“…This suggests that the BP lowering impact of exercise on day 1 persisted for 48 h. This adds to the theory that chronic exercise training effects on BP may merely reflect the acute PEH phenomenon with sustained BP reductions accumulating from each bout of exercise [24]. Indeed the magnitude of PEH to an acute bout is a strong predictor of how well one may respond to a chronic exercise training program [25][26][27]. In fact, when analyzed separately it has been shown that there is no difference in magnitude of BP (24-h ambulatory BP) reduction between the acute and chronic response from exercise [21,28].…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, the post-exercise duration was only for one hour, thus minimizing generalizability. This time frame was chosen however due to past data suggesting the lowest post-exercise BP value takes place within the first hour [32,33] and because of prior data suggesting that this immediate reduction could possible predict training responses [25][26][27]. Exercise duration for a single exercise session was not matched.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between baseline blood pressure and training induced change in blood pressure is not clear. Kiviniemi et al, suggested that baseline sympathetic predominance may predict the larger training induced decrease in DBP indicating that participants with sympathetic predominance may have greater potential to decrease neural sympathetic activity [20]. The present study was conducted in Innsbruck for European group and in Khon Kaen for Asian group.…”
Section: Discussionmentioning
confidence: 99%